PENGARUH LAYANAN KONSELING INDIVIDUAL TERHADAP TINGKAT STRES WARGA BINAAN ANAK LAKI-LAKI (KASUS NON NARKOBA) DI LAPAS ANAK PEKANBARU - Lestari Veronika; Zulfan Saam; Raja Arlizon (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: this study aims to determine the effect of individual counseling on the stress level of non-drug users in the prisons of Pekanbaru children, the research method used is the experimental research which is analyzed by qualitative research subject taken using sampling purposive as 5 non-drug boys in non-drug cases in prison of citizens of Pekanbaru residents the research is pre-test post-test one group design, which is done twice before being given treatment or treatment and after being given treatment post (post-test) with one subject group. This research is conducted by providing individualized counseling services that have been modified 5 times meeting. The results of this study indicate that there is an influence of individual counseling on the stress level of non-drug target boys in Pekanbaru prisons based on the results of questionnaire analysis and observations made by researchers. Before the counseling process ends 2 people assisted men non-drug cases in prisons of Pekanbaru children declared drop out.Key Words: Individual counseling, stress levels, Prison Cildren.